1998
DOI: 10.1097/00005373-199809000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Stable Pediatric Blunt Trauma Patients

Abstract: Mechanisms of injury seem to have limited value as predictors of injury severity in stable pediatric blunt trauma patients. A modified response level for these patients may prove to be a safe and practical alternative to current practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…13 Many (39%) described 2-tiered trauma team activation criteria. 5,8-10,16,17,21 A number of studies evaluated the accuracy of criteria categories including mechanism 6,8,18,19 and physiologic criteria 2 as well as simplified criteria including only respiratory compromise and intubation. 12 Two studies evaluated variations of the Pediatric Trauma Score, 11,15 and 2 studies applied the current ACS criteria to the trauma population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Many (39%) described 2-tiered trauma team activation criteria. 5,8-10,16,17,21 A number of studies evaluated the accuracy of criteria categories including mechanism 6,8,18,19 and physiologic criteria 2 as well as simplified criteria including only respiratory compromise and intubation. 12 Two studies evaluated variations of the Pediatric Trauma Score, 11,15 and 2 studies applied the current ACS criteria to the trauma population.…”
Section: Resultsmentioning
confidence: 99%
“…Some published criteria depended heavily on anatomic factors to identify trauma team activation criteria including 14 specific injuries, 2 but 6 criteria included no anatomic factors at all. 6,7,12-14,18…”
Section: Resultsmentioning
confidence: 99%
“…53,54 From previous studies of pediatric patients in which age has been considered a criterion for an automatic trauma response, 5558 it has been found that age (specifically young age) may not be an appropriate sole criterion for requiring a higher level of trauma care. There is, however, some literature suggesting a tiered approach to trauma center activation once a patient has reached the emergency department for a range of patient characteristics.…”
Section: Commentmentioning
confidence: 99%
“…Intervention-based measures have been found to perform better than the well-established major trauma definition [ 30 , 31 ], including as a means of evaluating TTA criteria [ 32 ]. Centers should review TTA criteria regularly to ensure that they identify patients who will benefit from a trauma team [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%